Psychoeducational Work Techniques in the Context of Executing Punishments, Which Are Alternative to Imprisonment: Historical Aspect - Natalya Evgenyevna Kolesnikova; Alexander Vasilyevich Agrashenkov (Управленческое консультирование)
Nowadays application of punishments, which are alternative to imprisonment, is developing in the Russian Federation. Russia has rather successful experience of implementing such punishments. Efficiency of suspended sentence and conditional release is confirmed by the fact that recidivism among probationers during having a record in special commandant’s offices didn’t exceed 3%; within the next three years after deregistration - 5-6%. Psychological follow-up of the Corrective Services (CS) activity has begun rather recently. In CS departments the psychological service has started functioning since 2010, and now the regulatory and legal framework requires modification and correction. The historical analysis of psychoeducational work techniques in the context of executing punishments which are not connected with incarceration is presented in the article. Such forms of educational work as patronage, activity of social inspectors, councils of people’s assessors, public councils are revealed and analyzed. Besides, the analysis of psychological work with convicts to the punishments, which are alternative to imprisonment, is given.